2017
DOI: 10.1080/09273948.2017.1348527
|View full text |Cite
|
Sign up to set email alerts
|

Uveitis in Patients with Retinitis Pigmentosa: 30 Years’ Consecutive Data

Abstract: Uveitis in RP patients is rare, but not uncommon. Coexistence of these disorders might support the inflammatory pathway in etiology of RP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
0
17
1
3
Order By: Relevance
“…Retinitis pigmentosa might be associated with uveitis and ME at any stage of the disease 156,157. The pathophysiology of this edema is poorly understood, it might be related to inflammatory reaction due to autoantibodies and abnormal vascular permeability 158.…”
Section: Therapeutic Managementmentioning
confidence: 99%
“…Retinitis pigmentosa might be associated with uveitis and ME at any stage of the disease 156,157. The pathophysiology of this edema is poorly understood, it might be related to inflammatory reaction due to autoantibodies and abnormal vascular permeability 158.…”
Section: Therapeutic Managementmentioning
confidence: 99%
“…It is initially manifested by symptoms of night blindness, followed by peripheral visual field constriction and by loss of central vision in the most advanced stages [ 10 ]. Several studies have also demonstrated that uveitis is not an uncommon condition in RP patients [ 11 , 12 , 13 , 14 ]. However, the underlying mechanism explaining why some patients with RP are prone to AU, and vice versa, is largely unknown and remains an important issue to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…In fluorescein angiography, leakage was found mainly in the posterior pole but also the periphery in most eyes with a typical RP [ 9 ]. Clinically relevant uveitis was found to be uncommon, with a uveitis prevalence of 0.26% in the RP patient cohort [ 10 ].…”
Section: Discussionmentioning
confidence: 99%